Composition and Percentage Comparison of Bycatch between Conventional Gillnets and Modified Gillnets - Afni Afriani; Irnawati Sinaga; Fandi Handika Arta (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Sibolga, as one of the major fishing port cities in North Sumatra, is an area where surface gillnets are commonly used in pelagic fishing operations. However, the use of gillnets currently faces significant challenges, including high bycatch levels and threats to the sustainability of pelagic fish ecosystems. This study employed an experimental fishing method, specifically surface gillnet trials. The trials were conducted using gillnets with mesh sizes of 2” and 2.5”. The results show that the modified gillnet with a 2.5-inch mesh size yields a significantly higher target catch percentage (HTU) of 73% compared to the conventional gillnet with a 2-inch mesh size, which yields only 27%. This significant difference highlights the importance of selecting the appropriate mesh size to optimize gear selectivity. The principle of geometric selectivity can explain the 46% difference in HTU between the two types of gillnets. Furthermore, the use of conventional gillnets with a 2-inch mesh size resulted in a higher HTS (62%) than modified gillnets with a 2.5-inch mesh size (38%). These data indicate that smaller mesh sizes tend to be less selective and capture more non-target species. A larger L value indicates this, compared to the length of the first fish caught (Lc), suggesting that the fishing practices employed do not threaten the sustainability of fish populations.